LIABILITY FOR BREACH OF OBLIGATIONS IN CIVIL LAW - Allambergenova Zamira Rasbergen qizi; Nuratdinov Muxametdin Ibraxim ugli (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the concept of liability for non-fulfillment of obligations, its importance, content and types of liability, the bases of liability, the opinions of scientists about it, the main conditions and issues in the application of liability are described.